Determining Effects of Leg Exercises to Increase Blood Circulation in The Feet of Diabetes Mellitus Patients - Hasnah Hasnah; Ambo Sau (Indonesian Contemporary Nursing Journal, 2017)
Introduction: Based on the routine surveillance of non-communicable diseases (NCDs) hospital based in South Sulawesi diabetes mellitus highest cause of death in the amount of 41.56%. Diabetes mellitus is a heterogeneous group of disorders characterized by an increase in blood glucose levels, or hyperglycemia. Method: This research is quasi experimental. Research design used in this research is non equivalent control group. The sampel size of this research twenty person, sampel devided into two groups with the one experimental grour and one control group, each group considerate of ten sampel. Result: Paired T test on blood circulation foot pre and post test in the intervention group. The result is the intervention group was obtained p-value of 0.001 or p <0.05, which means that there is significant influence before and after the exercise intervention feet. Conclusions: This study shows that a very effective leg exercises to improve blood circulation foot, strengthens leg muscles and ease of movement of joints. It is expected that the public, especially people with diabetes mellitus should do leg exercises independently and regularly, live a healthy lifestyle in order to prevent complications of diabetes mellitus is diabetic ulcers